Forms, Factors And Consequences Of Cheating In University Examinations: Insight From Open And Distance Learning Students - MOKULA, Lebeloane Lazarus Donald; LOVEMORE, Nyaumwe (The Turkish online journal of distance education TOJDE, 2014)
The present study narrated the forms, factors and consequences of cheating in university examinations by UNISA Open and Distance learning students from anecdotal data. The results showed that the perpetrators mostly used crib materials on paper, ruler and calculator cover. The factors that influenced examination cheating were gender, age range and regional locations of candidates. The consequences were monetary fines and suspension periods. The limitation of the study is that inferences are based on documented evidence only without verification through interviews. The study provides some recommendations that may provide Registrars of universities with insight to tighten up examination regulations so that the credibility of degrees universities offer is upheld through awarding degrees to deserving students only.